Web-Based Community Data Collection Information System at the Central Statistics Agency of Sragen Regency: Sistem Informasi Pengumpulan Data Masyarakat Berbasis Web di Badan Pusat Statistik Kabupaten Sragen - Satriyana, Putri; Naury, Chairullah; Purbiyanto, Eko (RADIANT: Journal of Applied, Social, and Education Studies, 2024)
The community data collection information system is a technological solution designed to efficiently collect, manage, and analyze information from various layers of the community. The main objective of this system is to support data-driven decision-making by facilitating the collection of accurate, fast, and measurable information. The limitation of manual community data collection at the Central Statistics Agency (Badan Pusat Statistik) in Sragen Regency has led to data damage, loss of data, and ambiguity in data due to the information being written on questionnaire papers using pencils. Due to the abundance of population data that needs to be stored and to support the performance of officers, there is a need for a computerized web-based system as a tool for officers to carry out their activities. The aim of this research is to design a Web-Based Community Data Collection Information System at the Central Statistics Agency in Sragen Regency. The researcher uses the Waterfall method in the system development process and the PHP programming language, along with the MySQL database. The system designed by the researcher is expected to produce an application that can accommodate all community data accessible via the web by administrators and field officers at the Central Statistics Agency in Sragen Regency.